Supervision in psychiatric practice : practical approaches across venues and providers - De Golia, Sallie G.; Corcoran, Kathleen M. (American Psychiatric Association Publishing, 2019)
This guide explores a range of supervisory techniques--from role-playing and working with process notes to live supervision and cotherapy--as well as a variety of venues--from inpatient and community-based settings to diverse administrative contexts and scholarly environments. It also features a thorough discussion of unique issues in supervision, as well as legal issues and the current state of professional development--back cover.